Studying on Learning Satisfaction in Teaching Keyboard Courses With Problem-Based Learning Teaching Mode - Ko, Chia-hui (Frontiers in Psychology, 2022)
With the learning characteristics of adults, such as self-directed learning, courses that are preferred in application and practice, this research explores the Problem-Based Learning (PBL) teaching method employed in adult keyboard music learning courses. This research established a research model and investigated the correlation of learning satisfaction with influencing factors such as teaching effectiveness, self-efficacy, and teamwork and verified teaching effectiveness, self-efficacy, and teamwork relationships. Research data has been collected from the keyboard music students of the two classes of the Arts & Culture Department in Open University of Kaohsiung (OUK). Data analysis was conducted in three stages: descriptive statistics, measurement model verification, and structural equation model. The results of the study found that teaching effectiveness has a significant impact on learning satisfaction. Teamwork also has a significant positive impact on learning satisfaction. However, the self-efficacy dimension has little effect on learning satisfaction. Finally, the results of the study found that teaching effectiveness and teamwork both have significant impacts on learning satisfaction. However, the self-efficacy dimension has little effect on learning satisfaction. The student-led presentations went smoothly and the results were quite remarkable, which became a reference for the implementation of other courses for adults in the future.